2012
DOI: 10.1172/jci58928
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic stress sensitizes murine cancers to hypomorphic suppression of ATR

Abstract: Oncogenic Ras and p53 loss-of-function mutations are common in many advanced sporadic malignancies and together predict a limited responsiveness to conventional chemotherapy. Notably, studies in cultured cells have indicated that each of these genetic alterations creates a selective sensitivity to ataxia telangiectasia and Rad3-related (ATR) pathway inhibition. Here, we describe a genetic system to conditionally reduce ATR expression to 10% of normal levels in adult mice to compare the impact of this suppressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
164
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 166 publications
(173 citation statements)
references
References 62 publications
9
164
0
Order By: Relevance
“…In contrast, several studies have now shown that, over a threshold, the RS induced by Myc, Ras, or cyclin E oncogenes can be cytotoxic (Gilad et al, 2010;Murga et al, 2011;Toledo et al, 2011;Schoppy et al, 2012), which would rather argue that oncogeneinduced RS limits transformation. The data reported here favor the latter view, supporting that oncogeneinduced RS is a toxic byproduct of transformation, which is not needed by the oncogenes to trans form, and which decreases the fitness of transformed cells.…”
Section: Resultsmentioning
confidence: 94%
“…In contrast, several studies have now shown that, over a threshold, the RS induced by Myc, Ras, or cyclin E oncogenes can be cytotoxic (Gilad et al, 2010;Murga et al, 2011;Toledo et al, 2011;Schoppy et al, 2012), which would rather argue that oncogeneinduced RS limits transformation. The data reported here favor the latter view, supporting that oncogeneinduced RS is a toxic byproduct of transformation, which is not needed by the oncogenes to trans form, and which decreases the fitness of transformed cells.…”
Section: Resultsmentioning
confidence: 94%
“…These data suggest that ATR can use a complex, and coordinated set of proteins involved in intra-S checkpoint function to maintain genomic integrity. In this scenario, we hypothesize that these approaches may be expanded to other cancer types, in which high levels of replicative stress, like oncogene-induced, genomic instability or repair deficiencies may further expand the therapeutic window for treatment activity (12,34,41). …”
Section: Discussionmentioning
confidence: 99%
“…Also, when MYC was inhibited through lentivirus-based shRNAs in human metastatic melanoma cell lines, the genes encoding enzymes important for dNTP metabolism were repressed and the amount of dNTPs were reduced (Mannava et al 2008). Last, Myc controls the ATR DNA repair pathway that is activated in response to specific single-stranded DNA produced during replication stress (Schoppy et al 2012). Components of this pathway are also potential therapeutic targets as their inhibition in cells with Myc overexpression can result in increased DNA damage and trigger an apoptotic response.…”
Section: Myc and Dna Damage And Repairmentioning
confidence: 99%